Validation of the SISRE-P Software for Teaching Reflection in Mathematical Didactics using the DELPHI Method - Rodriguez, Diana Isabel Rodriguez; Correa, Ximena Patricia Curay; Cubillos, Monica Alexandra Salto; Llangari, Jackeline Daisy Chiqui (Journal of Ecohumanism, 2024)
This research addresses the use of software in the mathematics education process, which has been growing in popularity and has proven to be a valuable tool to improve teaching and learning. The study aimed to validate the SISRE-P software in the teaching of mathematics, with the purpose of reducing the gap between theory and educational practice, and improving pedagogical practice. From the methodological point of view, a qualitative, cross-sectional and descriptive study was carried out, using the Delphi method for the validation of the instrument, which was applied to 36 teachers. For its development, a questionnaire was applied in the form of interviews, which were sent through Google Forms, through the process, they were analyzed to evaluate the effectiveness of SISRE-P. Within the results obtained, it is observed that the implementation of the SISRE-P software demonstrates its effectiveness to improve teaching practice in mathematics teaching. Recurrent participation in weekly reflective sessions, both in pedagogical pairs and with colleagues or individually, has strengthened the reflective process through methods such as class recording, collaborative conversations and records in field diaries. It is concluded that SISRE-P is an effective tool to enhance teaching practice in the teaching of mathematics. Its constant use in reflective sessions strengthens the process of teacher self-reflection and is fundamental within the constructivist pedagogical framework, focused on student autonomy and the active construction of knowledge.